Total recall. New practices of memory and imagination in Venice biennale 2013 - Sabolius, Kristupas (Religija ir kultūra, 2013)
The author examines the re-actualization of memory and imagination in contemporary art practices. Departing from the idea of “Encyclopedic Palace” proposed by Massimiliano Gioni, the main curator of Venice Biennale 2013, it aims to relate architecture, knowledge and memory through various forms of imagination. Focusing on the creative practices by Aurélien Froment and his work “Camillo’s Idea”, a film featuring a mnemonist in the Teatro Olimpico in Vicenza, who demonstrates her own feats of memory and recites the history of mnemonics, it analyses the problematic relationship among media images, mental states, and corporeal experiences. Bydeploying various theories and takes on the imaginary by Bernard Stiegler, Pietro Montani, Jean-Jacques Wunenburger, Joel Candau, this paper unfolds the dynamic interaction between symbolic imagination and mediated forms of life.
Keywords: memory; imagination; symbol; media; intermediality